PENGEMBANGAN MASYARAKAT DI BIDANG EKONOMI MELALUI MIGRASI (STUDI POLA MIGRASI PEDAGANG BURJO ASAL SINDANGAGUNG DAN GARAWANGI KUNINGAN DI YOGYAKARTA) - Asep Kurniawan (UIN Siber Syekh Nurjati Cirebon, 2019)
This research traced the migration of green bean porridge traders in Yogyakarta,why were they from Kuningan?To answer this question, things related to migration, such as type, motivation and purpose, need to be answered by research. The used theories were push-pull theory and chain theory. This study was an anthropological qualitative study with ethnographic methods.The research findings showed that green bean porridge traders in Papringan were migrant groups from Kuningan who built a network of group relations. This network was formally proven by the existence of an association (paguyuban Arya Kemuning) which accommodated green bean porridge traders. Implicitly, the network of green bean porridge traders could be seen from a sense of mechanical solidarity, which was formed by regional ethnicity. The chosen circulational migration was another proof of the existence of green bean porridge traders network in Yogyakarta. It was used as a solution for community development for economic prosperity.